Effects of different treatments on metabolic syndrome in patients with obstructive sleep apnea: a meta-analysis - Liu, Jianing; Xu, Jiahuan; Guan, Shibo; Wang, Wei (Frontiers in Medicine, 2024)
Background： Obstructive sleep apnea (OSA) and metabolic syndrome(MetS) often coexist, and the causal relationship between them is not yet clear; treatments for OSA include continuous positive airway pressure (CPAP), mandibular advancement device(MAD), surgery, and lifestyle intervention and so on. However, the effects of different treatments on metabolic syndrome in OSA patients are still under debate.Objectives: Review the effects of different treatments on metabolic syndrome in OSA patients by meta-analysis.: we searched articles in PubMed, Embase, Cochrane Library, CNKI, CBM, and Wanfang data from database construction to Feb. 2024.RevMan5.4 and Stata software were used to conduct a meta-analysis of 22 articles. 1 Result: A total of 22 articles were finally included. The results showed that CPAP treatment could reduce the prevalence of metabolic syndrome in OSA patients in randomized controlled trials (RCTs)(RR=0.82[95%CI, 0.75-0.90]; p < 0.01) and single-arm studies(RR=0.73[95%CI, 0.63-0.84]; p < 0.01). As for metabolic syndrome components, CPAP treatment reduces blood pressure, fasting glucose(FG), triglycerides (TG), and waist circumference(WC) but can not affect high-density lipoprotein cholesterol(HDL-C) levels. 2 Lifestyle intervention could significantly reduce the prevalence of metabolic syndrome in OSA patients (RR=0.60[95%CI, 0.48-0.74]; p < 0.01) and can lower blood pressure, fasting glucose, and waist circumference but can not affect the lipid metabolism of OSA patients. 3 Upper airway surgery can only reduce TG levels in OSA patients (MD=-0.74 [95% CI, -1.35 to -0.13]; p=0.02) and does not affect other components of metabolic syndrome. There is currently no report on the impact of upper airway surgery on the prevalence of metabolic syndrome. 4 No study has reported the effect of MAD on metabolic syndrome in OSA patients. Conclusion： We confirmed that both CPAP and lifestyle intervention can reduce the prevalence of MetS in OSA patients. CPAP treatment can lower blood pressure, fasting glucose, waist circumference, and triglyceride levels in OSA patients. Lifestyle intervention can lower blood pressure, fasting glucose, and waist circumference in OSA patients. Upper airway surgery can only reduce TG levels in OSA patients.